2017
DOI: 10.1016/j.cbi.2017.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Role of RAS/Wnt/β-catenin axis activation in the pathogenesis of podocyte injury and tubulo-interstitial nephropathy

Abstract: Renin-angiotensin system (RAS) plays a key role in the development and progression of chronic kidney disease (CKD). Recent studies have demonstrated activation of Wnt/β-catenin pathway by RAS in CKD. However, the underlying mechanisms of RAS and Wnt/β-catenin signaling interaction and their contribution to the pathogenesis of CKD have not been fully elucidated. Present study is designed to investigate the role of RAS/Wnt/β-catenin axis activation in tubulo-interstitial fibrosis and glomerulosclerosis by the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 54 publications
(42 reference statements)
2
69
0
Order By: Relevance
“…Our results indicated that AR treatment retarded renal fibrosis by downregulating inflammation and TGF-β1/Smad pathway in CKD rats [108]. Our further study demonstrated that alisol B 23-acetate treatment significantly amileriated podocytes and tubular epithelial cells by inhibiting activation of Wnt/βcatenin, oxidative stress and inflammation [109]. 25-O-methylalisol F is a new tetracyclic triterpenoid compound isolated from the AR.…”
Section: Targeting Tgf-β1/smad Signaling By Isolated Compoundsmentioning
confidence: 57%
“…Our results indicated that AR treatment retarded renal fibrosis by downregulating inflammation and TGF-β1/Smad pathway in CKD rats [108]. Our further study demonstrated that alisol B 23-acetate treatment significantly amileriated podocytes and tubular epithelial cells by inhibiting activation of Wnt/βcatenin, oxidative stress and inflammation [109]. 25-O-methylalisol F is a new tetracyclic triterpenoid compound isolated from the AR.…”
Section: Targeting Tgf-β1/smad Signaling By Isolated Compoundsmentioning
confidence: 57%
“…Additionally, it was also observed that ergone inhibited extracellular matrix accumulation in HK-2 cells and attenuated podocyte injury through inhibiting the activation of the Wnt/β-catenin signaling pathway induced by angiotensin II. 81 Taken together, these data indicate that tetracyclic triterpenoid and steroid compounds show significant antifibrotic properties in renal fibrosis.…”
Section: Wnt Signaling Pathwaymentioning
confidence: 82%
“…Our recent study demonstrated that triterpenoid was the main component of AR, and further study showed that the novel tetracyclic triterpenoid 25‐O‐methylalisol F inhibited EMT by suppressing the Wnt/β‐catenin signaling pathway as well as the phosphorylation of Smad3 signaling in both NRK‐52E and NRK‐49F cells (Figure and Table ). Additionally, it was also observed that ergone inhibited extracellular matrix accumulation in HK‐2 cells and attenuated podocyte injury through inhibiting the activation of the Wnt/β‐catenin signaling pathway induced by angiotensin II . Taken together, these data indicate that tetracyclic triterpenoid and steroid compounds show significant antifibrotic properties in renal fibrosis.…”
Section: Small Molecules Against Emtmentioning
confidence: 99%
“…The results suggested that SOST/β‐catenin pathway might also be involved in the action of TSG on osteogenesis. Additionally, the recent studies showed the link between the local RAS and β‐catenin pathway in kidney (Chen et al, ; Wang et al, ), and the natural products contained in traditional herbal medicine, such as triterpenes (PZG and PZH) from Poria cocos (Wang et al, ) and 25‐O‐methylalisol F from Alismatis rhizome (Chen et al, ), were found to act as novel RAS inhibitors in attenuating renal fibrosis. The effects of TSG on the cross talk between these two pathways in bone need to be further investigated for better understanding the role and the action mechanism of TSG in maintaining bone health.…”
Section: Discussionmentioning
confidence: 99%